Consideration in treatment decisions for refractory Mycoplasma pneumoniae pneumonia - Hye-Kyung Cho (The Korean Pediatric Society, 2021)
Mycoplasma pneumoniae (MP) is the most common cause of childhood bacterial pneumonia. Although macrolide is known to be effective as a first-line therapy, the proportion of macrolide resistance in MP pneumonia has strikingly increased during recent 2 decades in East Asia. This is challenging to physicians since they have to decide more often whether to use secondary treatment. Diagnostic methods to detect macrolide-resistance of MP are currently not available in Korean hospitals. Even in the diagnosis of MP infection, both serologic and molecular test have limitation: inability to differentiate current illness from carriage or asymptomatic infection. Combining these 2 diagnostic methods and excluding infection caused by other respiratory pathogens allow a more reliable diagnosis. This effort is even more demanding in recent years to keep children from unnecessary exposure to secondary antibiotics. Although several observational studies have reported that tetracycline and fluoroquinolone, which are considered in the treatment of refractory MP pneumonia, have efficacy of shortening the duration of fever and respiratory symptoms, those findings need to be proven by well-designed prospective studies. The use of tetracycline and fluoroquinolone in children is generally tolerable, as supported by many observational data. However, since concerns about side effects still remain, careful consideration about benefits and risks is needed to decide their use.